Transforming Screening, Risk Stratification, and Treatment Optimization in Chronic Liver Disease Through Data Science and translational Innovation - Addissouky, Tamer A. (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Background: Chronic liver diseases continue to face challenges in prognosis, treatment selection, disease mechanisms, screening, and therapeutic optimization. Promising innovations could address these gaps through data integration and novel analytic approaches.Main Body: MAPS-CRAFITY integrating clinical variables, AFP, and CT/MRI findings, and transformer modeling of RFA data improve HCC outcome prediction to guide management. Analyses revealing IL21R as a PBC susceptibility gene and implicating dysfunctional VWF processing in portal hypertension deliver mechanistic insights. Quantifying childhood MAFLD informs screening needs, while supporting use of G6PD deficient liver donors enables transplantation access expansion through risk stratification. Updating Baveno criteria enhances PBC prognosis, and an HCC prognostic score identifies optimal RFA candidates to maximize treatment efficacy.Conclusion: Recent research leverages diverse data types, genetics, imaging, and machine learning to develop integrated predictive systems that allow more personalized therapy selection. Elucidating molecular pathways provides therapeutic targets and prognostic biomarkers. Evidence-based screening and risk models facilitate delivering tailored interventions. Optimization of current modalities through prognostic validation and patient selection improves real-world effectiveness. Multifaceted modern research approaches promise to address unmet needs and transform hepatology care.